Analysis of the Modeling Outputs of Shape Factor Effect on Flow Structure between Bridge Piers (Journal of University of Babylon for Engineering Sciences, 2018)
The submerged flow through piers is a weak turbulent flow. In this flow viscosity damps the flow fluctuations caused by obstacle. The flow conditions are affected substantively by pier shape. For viewing the structural characteristics of flow, twenty two different piers shape has been studied experimentally and modeled numerically. Classical k-ε turbulence model has been employed and comparison has been carried between predicted free surface profiles and laboratory measurements and so has been done with the discharge. The determinants of flow structure that predicted such as viscous length, turbulent energy, turbulence energy percent, turbulent dissipation, energy coefficient and momentum coefficient have been investigated. The investigation leads that these determinants are well reflectors for pier shape and they are highly correlated to flow discharge and Froude number with adjusted coefficient of determination equals to 0.957 and 0.949 respectively. Statistical results show that piers of sudden tail expansion cause an average increase of 16% and 8.5% in the relative values of energy and momentum coefficients respectively compared with gradually expanded, while an average increase of 2%, 23% and 6% in maximum values of viscous length, turbulent dissipation and turbulence energy percent respectively. In addition 10 volumetric shape factors have been calculated and then automatic linear regression has been carried with the structural determinants. The adjusted  of five shape factors have exceeded the 80% and the best one is the elongation shape factor.